Ugovor vesti v slovenskih javnih lekarnah - Kodrič, Ana (Farmacevtski vestnik, 2023)
In medicine, conscientious objection is understood as the refusal of certain medical treatment that is not in accordance with a medical worker’s conscience. The aim of this study was to investigate the knowledge, use and attitudes of Slovenian community pharmacists towards conscientious objection. For this purpose, we conducted a focus group, the content of which was developed based on a systematic literature review and an online survey of a purposeful sample of Slovenian pharmacists. The number of pharmacists in Slovenia who practice conscientious objection is unknown. However, the focus group panellists estimate that there are very few. Enforcement of conscientious objection is often associated with a worse attitude from colleagues and employers, mainly because of the demanding work organization and fear of abuse. The results show a need for a clearer definition of the conscientious objection practice and education, which would contribute to better knowledge and, consequently, a higher acceptance of this ethical institute in the community pharmacy practice.
Keywords: Farmacevti; javne lekarne; Lekarne; lekarniški farmacevt; ugovor vesti